Multi-factor Authentication as a Service for Cloud Data Security - Rajani, Sajjan; Ghorpade, Vijay; Dhange, Madhuri (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is a one of the emerging technology in IT industries nowadays. Cloud computing offers a wide range of services to its users. It delivers on demand services over internet with low cost investments. One of the service provided by cloud is data storage. But security and privacy of cloud data are main issues as cloud does not ensure the security aspects like confidentiality, integrity, identification etc. The cloud computing also enables users to access data from the cloud servers. To protect data access by unauthorized users, authentication plays an important role. Authentication is a first step for data security, through which user can establish proof of identities prior data access from system. In cloud computing environment, conventional authentication methods do not provide strong security against today’s most modern means of attacks. So cloud needs a dynamic approach for user authentication which should include more than one credentials for authentication. In this paper, we propose a data security architecture with a robust, dynamic and feasible Multi-Factor Authentication (MFA) scheme which integrates more than one factors like knowledge, possession, location and time, for cloud user authentication.